2021
DOI: 10.1016/j.cej.2020.127357
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming mass and photon transfer limitations in a scalable reactor: Oxidation in an aerosol photoreactor

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…This effectively prolonged the lifetime of the nebula and simultaneously assisted with collection in the product vessel. Recently, another photoreactor design was reported that also used nebulization to produce aerosols to efficiently harvest the irradiated light . The general concept of this reactor was very similar to the NebPhotOX, but a key difference in reactor operation was the light irradiation.…”
Section: Reactor Design and Scale-upmentioning
confidence: 99%
See 1 more Smart Citation
“…This effectively prolonged the lifetime of the nebula and simultaneously assisted with collection in the product vessel. Recently, another photoreactor design was reported that also used nebulization to produce aerosols to efficiently harvest the irradiated light . The general concept of this reactor was very similar to the NebPhotOX, but a key difference in reactor operation was the light irradiation.…”
Section: Reactor Design and Scale-upmentioning
confidence: 99%
“…Recently, another photoreactor design was reported that also used nebulization to produce aerosols to efficiently harvest the irradiated light. 170 The general concept of this reactor was very similar to the NebPhotOX, but a key difference in reactor operation was the light irradiation. Whereas the NebPhotOX used external irradiation, this design consists of an immersion well-type jacketed glass vessel where a UV-A lamp was placed in the center and the aerosol was passed through the annular hole (the jacket).…”
Section: Custom Reactorsmentioning
confidence: 99%
“…The ray tracing model was employed to predict the light absorption in single and two-phase flow at the gas fractions βG=0. 25 [RB]•10 5…”
Section: Ray Tracing Model Validation Using Dma Photooxidation Experi...mentioning
confidence: 99%
“…gasliquid-solid) [8,[12][13][14]. The optimization of operating conditions was studied for various gas-liquid flow patterns such as annular [10,[15][16][17], Taylor [18][19][20], bubbly flow [21][22][23] and more recently, aerosols [24,25]. Based on these experimental studies, the parameters determining the yield and selectivity of the oxygenated/oxidized products are the reactor channel size, the sum of liquid and gas flow rates, gas to liquid volumetric ratios, gas-liquid flow pattern, light intensity, photosensitizer concentration and oxygen pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[31] To overcome this issue, oscillatory flow conditions or ultrasound might be used to provide both an intense mass transport together with long residence time. [32][33][34] Scale-up strategies include classical numbering-up of capillary flow reactors as well as dedicated tank reactors with larger volumes. Various reactor designs have been shown to be scalable and were applied on industrial scale.…”
Section: Reactor Designmentioning
confidence: 99%